Preparation of ZIF67-modified phosphate compounds for enhancing fire safety of strandboards - Tian, Feiyu; Wu, Yutao; Zhu, Chunfeng; She, Yanan; Jin, Yuanyuan; Wang, Bingbing; Chen, Hao; Xu, Haocheng; Liu, Yingpeng; Wang, Shaocong; Xu, Xinwu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•In-situ assembled APz@ZIF67 provided whole-process fire prevention from pyrolysis to flaming;•APz@ZIF67 exhibited synergistic enhancement in LOI and bending strength other than APP;•Highly-porous ZIF67 absorbed toxic gases and helped suppress smoke during combustion;•ZIF67 inspired foamed char layer for burnt strandboard locking gas evacuation. Wood strandboard as a typical green building material is facing challenges as for its low fire safety. Conventionally applied flame retardants such as ammonium polyphosphate (APP) have limitations due to insufficient smoke control and adverse effects on the mechanical properties of strandboards. Herein, a core–shell structure flame retardant (APz@ZIF67) was synthesized by growing Co2+ on the surface of piperazine-modified APP (APz). At a same loading level of 10 wt%, the properties of strandboards containing APP, APz, and APz@ZIF67 were specifically analyzed and compared with untreated boards. It’s found that APz@ZIF67 exhibited synergistic enhancement of strandboards both in mechanical and flame-retarding properties other than APP or APz. APz@ZIF67 modified strandboards showed increased bending strength and modulus by 70.37 % and 19.65 %, respectively. Strain migration analysis by digital image correlation disclosed the higher stress transfer efficiency. Meanwhile, the limiting oxygen index of strandboards increased by 71.37 %, reaching 48.55 %. The mean heat release rate decreased by 48.61 %, and the total smoke rate decreased by 43.78 %. APz@ZIF67 helped patch the cracks in wood cells, preventing the evacuation of heat and gases through the char layers on the surface of burnt strandboards. Additionally, the highly porous ZIF67 attached to APz reduced production of toxic gases during the pyrolysis process of wood strands. The above findings confirm the potential applicability of metal–organic frameworks (MOFs) in enhancing intumescent flame retardants, and provide a state-of-the-art pathway to manufacture fire-safety wood composites with balanced mechanical properties.